Surgical Lip Repositioning in Search of Aesthetics - A Case Series - SK Aziz Ikbal; Zeba R. Siddiqui; Siddhartha Dutta; Tasneem Fatima; Roopanshi Mehrotra; Surendra K. Yadav (Wolters Kluwer Medknow Publications, 2024)
Introduction The gummy smile (GS) or excessive gum visibility (EGV) is an aesthetic concern that affects an individual's attractiveness and personality. Treatment Planning Lip Repositioning surgery (LRP) is a less invasive surgery that can be attributed to treating EGV due to hypermobile lip muscles or mild-to-moderate vertical maxillary excess (VME). Three patients went through LRP surgery by stripping overlying mucosa from the buccal vestibule, followed by suturing the lip mucosa to the mucogingival junction (MGJ), creating shallow vestibule and restricted muscle pull and reducing gingival visibility (GV) during a smile. Follow-up Three months of follow-up showed a satisfactory result with 3.67 ± 0.58 mm mean reduction in GV.